Thermal energy storage properties of a capric acid/stearic acid binary system and a 48# paraffin/liquid paraffin binary system. Issue 7 (9th August 2017) - Quanying, Yan; Wanyu, He; Xiao, Wang
ABSTRACT: In this paper, the phase change temperature, latent heat and thermal stability of a capric acid/stearic acid binary system and a 48# paraffin/liquid paraffin binary system were experimentally studied. The experimental results showed that the phase change temperature and phase change latent heat change with the content of the component. The phase change temperatures of binary mixtures change in a wide range, so they can be used in different fields by adjusting the mixing ratio. The phase change latent heat of fatty acid mixtures is higher than that of paraffin mixtures. The thermal stability of fatty acid mixtures is better than that of paraffin mixtures. The mixtures used in the phase change material wall or the phase change material floor as energy storage materials were given in the paper.